2000
DOI: 10.1093/ortho/27.4.315
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Skeletal Relationships in a Group of Young People with Hypodontia

Abstract: The objective of this investigation was to examine the dentofacial features of a group of patients with hypodontia, in particular assessing whether cephalometric analysis confirmed the clinical assumption of a reduced lower face height, and to determine the relationship of these facial features with different numbers of missing teeth. It took the form of a cephalometric study, undertaken in a dedicated Dental Hospital clinic for patients with hypodontia. The study group comprised 59 patients seen on the Hypodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
50
1
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 8 publications
7
50
1
13
Order By: Relevance
“…In the present study, all three hypodontia groups showed a significant reduction in the SNB angle compared with the controls. This disagree with the findings of Wisth et al, 27 Nodal et al, 30 Chung et al 31 and Yüksel and Ucem, 36 who founds no changes in SNB, but confirms those of Bondarets and Mc Donald, 24 who showed decreased SNB angle in persons with hypodontia. In individuals with agenesis persist continued reductions of values of ANB angle.…”
contrasting
confidence: 53%
See 4 more Smart Citations
“…In the present study, all three hypodontia groups showed a significant reduction in the SNB angle compared with the controls. This disagree with the findings of Wisth et al, 27 Nodal et al, 30 Chung et al 31 and Yüksel and Ucem, 36 who founds no changes in SNB, but confirms those of Bondarets and Mc Donald, 24 who showed decreased SNB angle in persons with hypodontia. In individuals with agenesis persist continued reductions of values of ANB angle.…”
contrasting
confidence: 53%
“…A decrease in vertical jaw relation and mandibular plane inclination in persons with severe hypodontia was observed by Øgaard and Krogstad 25 and Nodal et al 30 Chung et al 31 and Acharya et al 32 found that severe hypodontia had a significant effect on a skeletal relationship.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations